Frekuensi Penggunaan Obat Antifungal untuk Dermatofitosis pada Kucing di Klinik Hewan Starvet Bogor Tahun 2017 dan 2018 - Miyati Sofariah; Bayu Febram; Wiwin Winarsih (Jurnal Health Sains, 2021)
Dermatofitosis is a superficial fungal infection of the skin that is often found attacking pets such as cats. The disease is easy to occur in an atmosphere with high temperatures and humidity. Administration of antifungal drugs is usually done to treat and prevent cases of dermatofitosis. The purpose of this study is to describe the frequency of use of antifungal drugs in handling cases of dermatofitosis in veterinary clinics of research objects. The research was conducted descriptively using 39 medical record data from patients infected with dermatofita. The results showed antifungal drugs used for cases of dermatofitosis as much as twice the use of ketoconazole, 25 times the use of itraconazole, 11 times the use of blended ointments, and one use of griseofulvin. Based on the results of the study, itraconazole is the most widely used antifungal drug to handle cases of dermatofitosis in veterinary clinics